Comparison of Glycine Versus Sterile Water Use in Transurethral Resection of the Prostate: A Cross Sectional Study - Bhatta, Pashupati Nath; Yadav, Umesh Kumar; Raya, Akash; Yadav, Aditya Prakash; Karki, Rishi Kumar (Med Phoenix, 2022)
Introduction All endoscopic surgery in urology needs irrigant fluid for clear visibility and to wash out the blood and debris. Glycine 1.5% is widely accepted but sterile water is cheaper and easily available. All types of irrigants are responsible to cause electrolyte disturbance to different degrees. In our study, we compare the glycine 1.5% with sterile water as irrigant fluid. Materials and Methods In this prospective observational study, 64 patients were included with 31 patients in the sterile group and 33 patients in the Glycine group. Hemoglobin, sodium, potassium was analyzed postoperatively after 6 hours. Weight of prostate, resection volume, the volume of fluid, and resection time was calculated. Results There were changes in the parameter of hemoglobin and sodium but were not statically significant whereas the change in potassium was statically significant in both groups. Conclusion Sterile water is a safe inexpensive and easily available fluid for TURP as compared to glycine 1.5%. The study did not show any significant difference in using both fluids our sample size was small so needs a similar study with a large sample size to confirm the observation.